A stable home-base promotes allocentric memory representations of episodic-like everyday spatial memory. - Broadbent, Nicola; Lumeij, Lucas Berend; Corcoles, Marta; Ayres, Alice I; Bin Ibrahim, Mohammad Zaki; Masatsugu, Brittany; Moreno, Andrea; Caramés-Tejedor, José María; Begg, Elizabeth; Strickland, Lauren; Mazidzoglou, Theofilos; Padanyi, Anna; et al. (European Journal of Neuroscience, Wiley, 2020)
A key issue in neurobiological studies of episodic-like memory is the geometric frame of reference in which memory traces of experience are stored. Assumptions are sometimes made that specific protocols favour either allocentric (map-like) or egocentric (body-centred) representations. There are, however, grounds for suspect- ing substantial ambiguity about coding strategy, including the necessity to use both frames of reference occasionally, but tests of memory representation are not rou- tinely conducted. Using rats trained to find and dig up food in sandwells at a par- ticular place in an event arena (episodic-like 'action-where' encoding), we show that a protocol previously thought to foster allocentric encoding is ambiguous but more predisposed towards egocentric encoding. Two changes in training protocol were examined with a view to promoting preferential allocentric encoding—one in which multiple start locations were used within a session as well as between sessions; and another that deployed a stable home-base to which the animals had to carry food re- ward. Only the stable home-base protocol led to excellent choice performance which rigorous analyses revealed to be blocked by occluding extra-arena cues when this was done after encoding but before recall. The implications of these findings for studies of episodic-like memory are that the representational framework of memory at the start of a recall trial will likely include a path direction in the egocentric case but path destination in the allocentric protocol. This difference should be observable in single-unit recording or calcium-imaging studies of spatially-tuned cells.
Keywords: Hipocampo (Cerebro); Memoria; Event arena; Frames of reference; Hippocampus; Path integration; Rats